Mas-mas village tour guides: perception on the profession, roles and learning needs - Thohri, Muhammad; Hadi, Marham Jupri (Institut Pariwisata dan Bisnis Internasional, 2022)
Research on tourism suggests that tourist guides are key representatives in the tourism industry in that they have contributed significantly to the satisfaction of visitors and are believed to determine whether or not the tourist will revisit destinations. The present study sought to investigate the perception of local tour guides Mas Mas village pertaining to their future carrier as tour guides and the roles they played in the profession. It also assessed the perceived learning needs as tour guides. There were five local tour guides and two potential employers taking part in this study. Data were collected through Focus Group Discussion and semi-structured interviews and were analyzed by employing the five-phased cycle of qualitative data analysis. The findings of this study suggested that being a professional tour guide is a promising career and a prestigious career despite encountering negative perception from the local community. It also revealed the tour guides played as key factor to develop village based tourism. However, they believed to be in need of further training